Análise não-linear de estruturas laminares pelo método dos elementos finitos - Wrobel, Luiz Carlos (1977)
ln this work, the finite element method is applied to problems involving the geometrically non-linear behaviour of surface structures, subjected to static and dynamic loads. Two kinds of formulations are studied. ln the first one, through isoparametric degenerated elements, the tridimensional theory of elasticity is directly used. There are no restrictions for the magnitude of the deformations. The other one, derived from the von Kármán strain expressions for large deflections of thin plates, is limited to problems involving small deformations. Results from several analysis are presented. Advantages and limitations of the developed aproximations are discussed, as well as the efficiency of the implemented models.